2012
DOI: 10.1093/aje/kwr493
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Perinatal Risk Factors for Pyloric Stenosis and Their Influence on the Male Predominance

Abstract: Pyloric stenosis occurs with a nearly 5-fold male predominance. To what extent this is due to environmental factors is unknown. In a cohort of all children born in Denmark, 1977-2008, the authors examined the association between pre- and perinatal exposures and pyloric stenosis and investigated whether these factors modified the male predominance. Information on pre- and perinatal factors and pyloric stenosis was obtained from national registers. Poisson regression models were used to estimate rate ratios. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
38
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 33 publications
3
38
0
4
Order By: Relevance
“…Previous literature suggested that preterm infants rarely present with IHPS (11,12). Several recent epidemiological studies have found variable evidence that prematurity might be associated with increased risk of developing IHPS, although this association remains unclear (7,8,13,14).Full-term infants with IHPS typically present in the first 2-7 wk of life (7). The presentation age of preterm infants that develop IHPS is defined less clearly.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous literature suggested that preterm infants rarely present with IHPS (11,12). Several recent epidemiological studies have found variable evidence that prematurity might be associated with increased risk of developing IHPS, although this association remains unclear (7,8,13,14).Full-term infants with IHPS typically present in the first 2-7 wk of life (7). The presentation age of preterm infants that develop IHPS is defined less clearly.…”
mentioning
confidence: 99%
“…The presentation age of preterm infants that develop IHPS is defined less clearly. Some studies suggest that preterm infants may present with IHPS symptoms at a later chronological age than term infants, but the differences between presentation times in full-term and preterm infants are poorly characterized (7,8,11,(13)(14)(15). Using data from the Military Health System database, this study aims to examine the associations between prematurity and IHPS, and to investigate both gestational age (GA) and chronological age of IHPS among premature infants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date none of the theories fully explains the development of the disease [2] [4]. On the other hand, Krohg and collaborators listed a number of risk factors for the development of HPS, including: male gender, the use of macrolides, and bottle feeding, without having been able to clarify whether the cause is infant formula per se or technical supply [5] [6]. In addition to the vomiting, the disease may be accompanied by hypochloremic alkalosis and indirect hyperbilirubinemia [7].…”
Section: Discussionmentioning
confidence: 99%
“…Si el estudio se realiza de forma clasificatoria de diagnósticos, las más frecuentes serían las Anomalías del Aparato Circulatorio 13 , igual que la aparición en otras edades, o Anomalías en Aparato Urinario. Si el estudio lo realizamos por diagnóstico, el más frecuente es la Estenosis Pilórica Hipertrófica y con una clara diferencia de frecuencia, predominante en el sexo masculino, aunque esto es bien conocido en la etiopatogenia de esta anomalía 14 . Es coherente que el servicio hospitalario con más ingresos sea el de Cirugía Pediátrica, puesto que la mayoría de las anomalías congénitas tiene como tratamiento la cirugía y las edades de los pacientes son fundamentalmente pediátricas.…”
Section: Discussionunclassified